2016
DOI: 10.4038/jpgim.8097
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Knowledge on Hypertension, its consequences and management practices among hypertensive patients - A descriptive study

Abstract: Background Hypertension is an important public health challenge and is a major risk factor for many other diseases. Lack of knowledge on the dangers of untreated hypertension, the benefits of better control and poor management practices are barriers for effective hypertensive care. Objective The aim of the study was to describe the level of knowledge on the disease, its complications and management strategies among hypertensive patients attending Medical Clinics at Teaching Hospital, Batticaloa, Sri Lanka. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 12 publications
3
8
2
Order By: Relevance
“…The results were highlighted in a previous study in Northern Sri Lanka which showed that 40.5% of patients were unaware of hypertensive status even though 69.5% had adequate knowledge about hypertension [ 9 ]. Another study among 424 hypertensive patients in Eastern Sri Lanka also showed that 92% of people had inadequate knowledge on the disease, its complications, and management strategies of hypertension with a overall knowledge score of <50% [ 10 ] which is in contrast to our findings. Another study among 525 hypertensive patients in 3 different healthcare systems over a 1-year period showed a significant association between BP control and knowledge about normal BP [ 11 ].…”
Section: Discussioncontrasting
confidence: 99%
“…The results were highlighted in a previous study in Northern Sri Lanka which showed that 40.5% of patients were unaware of hypertensive status even though 69.5% had adequate knowledge about hypertension [ 9 ]. Another study among 424 hypertensive patients in Eastern Sri Lanka also showed that 92% of people had inadequate knowledge on the disease, its complications, and management strategies of hypertension with a overall knowledge score of <50% [ 10 ] which is in contrast to our findings. Another study among 525 hypertensive patients in 3 different healthcare systems over a 1-year period showed a significant association between BP control and knowledge about normal BP [ 11 ].…”
Section: Discussioncontrasting
confidence: 99%
“…For example, approximately one-third of Turkish patients with arterial hypertension had poor knowledge about their disease, and very few patients (6.6%) had adequate knowledge [16]. In Spain, approximately 92% of patients with arterial hypertension had inadequate knowledge about their disease, while very few patients (5.2%) had moderately good knowledge, and only 2.6% had good knowledge [17]. All these data indicate that patients in developed counties have a better knowledge about arterial hypertension than people in underdeveloped or developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Hypertension Fact Questionnaire was used to collect data which was designed as a tool, using the existing literature, practicing physicians and cardiologists to assess the knowledge and awareness among the hypertensive patients. 5 7 The questionnaire was initially designed in English and then translated to Sinhala and Tamil language. The questionnaire consists of 14 questions with different appropriate responses to assess the patients’ knowledge and 12 questions with different appropriate responses to assess the patients’ awareness on hypertension.…”
Section: Methodsmentioning
confidence: 99%
“…Their medication adherence and the reasons for non-adherence were studied using Medication Adherence Scale. 5 7 This questionnaire consists of several questions with “yes” or “no” responses and a set of open-ended questions for reasons for nonadherence. The score for the scale range within low (<6), medium (6 to <8) and high (8) adherence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation